2020
DOI: 10.22460/project.v3i5.p534-545
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students Perceptions on Extensive Reading Strategy in Vocabulary Class

Abstract: Vocabulary is one of the essential elements of English Language Teaching. It is therefore important to ensure that the students are able to obtain sizable vocabulary knowledge during their academic performance. Extensive reading strategy played a major role in that process. Two research problems were proposed in this study. The first is to know the effectiveness of extensive reading strategy in vocabulary class. The second is to discover the significant improvement of English Language Education students’ vocab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The Wattpad feature that allows users to choose books independently based on their reading level and interests boosts their motivation and interest in reading. Wijaya's (2020) research suggests that offering a flexible selection of texts is crucial to maintaining students' high reading motivation and positive perception of reading. Also İlter (2015) found that the Wattpad application provides many genres of stories and novels, making participants happy with the Wattpad application, plus the use of internet access, which is helpful if used well.…”
Section: Close-ended Questionnairementioning
confidence: 99%
“…The Wattpad feature that allows users to choose books independently based on their reading level and interests boosts their motivation and interest in reading. Wijaya's (2020) research suggests that offering a flexible selection of texts is crucial to maintaining students' high reading motivation and positive perception of reading. Also İlter (2015) found that the Wattpad application provides many genres of stories and novels, making participants happy with the Wattpad application, plus the use of internet access, which is helpful if used well.…”
Section: Close-ended Questionnairementioning
confidence: 99%